2003
DOI: 10.1007/s00595-003-2569-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of 5-Fluorouracil and Cisplatin Synergism for Advanced Gastrointestinal Cancers Using a Collagen Gel Droplet Embedded Culture

Abstract: Our findings suggested that the efficacy of the combined treatment with 5-FU and CDDP can be predicted by the in vitro chemosensitivity test and that a synergistic effect might be associated with the induction of apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…One of the advantages of CD-DST, compared to previous anticancer drug sensitivity tests, is that it favors the growth of tumor tissues in long-term cultures, due to its use of a three-dimensional growth assay with an image analysis device that is able to differentiate between cancer cells and fibroblasts (8). Previous studies reported that CD-DST may be useful when devising optimal treatment strategies for ovarian (9) or gastrointestinal cancer (1012). However, the clinical utility of CD-DST in the prediction of the response to adjuvant chemotherapy for colorectal cancer remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…One of the advantages of CD-DST, compared to previous anticancer drug sensitivity tests, is that it favors the growth of tumor tissues in long-term cultures, due to its use of a three-dimensional growth assay with an image analysis device that is able to differentiate between cancer cells and fibroblasts (8). Previous studies reported that CD-DST may be useful when devising optimal treatment strategies for ovarian (9) or gastrointestinal cancer (1012). However, the clinical utility of CD-DST in the prediction of the response to adjuvant chemotherapy for colorectal cancer remains to be determined.…”
Section: Introductionmentioning
confidence: 99%